Driving CARs with alternative navigation tools – the potential of engineered binding scaffolds. (31st August 2020) - Zajc, Charlotte U.; Salzer, Benjamin; Taft, Joseph M.; Reddy, Sai T.; Lehner, Manfred; Traxlmayr, Michael W.
Abstract : T cells that are genetically engineered to express chimeric antigen receptors (CAR T cells) have shown impressive clinical efficacy against B‐cell malignancies. In contrast to these highly potent CD19‐targeting CAR T cells, many of those directed against other tumor entities and antigens currently suffer from several limitations. For example, it has been demonstrated that many scFvs used as antigen‐binding domains in CARs show some degree of oligomerization, which leads to tonic signaling, T cell exhaustion, and poor performance in vivo . Therefore, in many cases alternatives to scFvs would be beneficial. Fortunately, due to the development of powerful protein engineering technologies, also non‐immunoglobulin‐based scaffolds can be engineered to specifically recognize antigens, thus eliminating the historical dependence on antibody‐based binding domains. Here, we discuss the advantages and disadvantages of such engineered binding scaffolds, in particular with respect to their application in CARs. We review recent studies, collectively showing that there is no functional or biochemical aspect that necessitates the use of scFvs in CARs. Instead, antigen recognition can also be mediated efficiently by engineered binding scaffolds, as well as natural ligands or receptors fused to the CAR backbone. Finally, we critically discuss the risk of immunogenicity and show that the extent of nonhuman amino acid stretches in engineered scaffolds—even in those based on nonhuman proteins—is more similar to humanized scFvs than might be anticipated. Together, we expect that engineered binding scaffolds and natural ligands and receptors will be increasingly used for the design of CAR T cells. Abstract : A large body of evidence has accumulated, demonstrating that there is no biochemical or functional requirement for the use of scFvs in CARs. Instead, highly potent CARs have been constructed based on several engineered non‐immunoglobulin‐based binding scaffolds. This review also includes a critical discussion on the risk of immunogenicity associated with different types of engineered binding domains and humanized or human scFvs.